Women with disabilities' experiences of gender-based violence in Cape Town, South Africa - Van Der Heijden, Ingrid (Department of Public Health and Family Medicine, 2019)
Background: Little is known about violence against women with disabilities in South Africa. Given that South Africa has a high prevalence of gender-based violence (GBV), especially intimate partner violence (IPV), there is a need to highlight the violence experiences of women with disabilities within their communities, intimate partnerships, and other settings. Aims: The aim of the thesis was to investigate how South African women with disabilities experience GBV. In doing so, the study’s objectives were to highlight the nature and forms of violence they experience, the social constructions of women with disabilities’ intimate partner relationships, and the barriers and enablers to GBV support they may encounter. Methods: This thesis takes the form of a qualitative research study that was conducted with 30 women with physical and sensory disabilities, and 19 disability and GBV service providers in Cape Town, South Africa. Repeat in-depth interviews and focus groups followed a narrative approach that was used to elicit participants’ stories, perspectives and lived experiences. Thematic analysis was conducted on the data, and interpretation of the data used an intersectional framework, with an emphasis on social approaches to disability and resistance theories. Findings: Published or submitted papers included in the thesis reveal how women with disabilities in South Africa may experience additional layers of GBV because of their disability status, and consider how gender inequality, disability stigma, and disability-specific forms of abuse shape participants’ lives and experiences of violence (Paper 1). The thesis claims that, while women with disabilities are vulnerable to GBV, particularly IPV, some women have agency and are able to manage disability stigma and intimate partnerships to avoid acts of violence (Paper 2). The thesis finds that, while women with disabilities do seek help after IPV and sexual violence, they encounter unique barriers to GBV service-provision. Service providers and women with disabilities acknowledge various limitations to providing inclusive and accessible services to women with disabilities who experience violence (Paper 3). The thesis also makes a series of recommendations for undertaking ethical GBV research with women with disabilities, and argues for the need to review current ethical guidelines to facilitate future disability-inclusive GBV research (Paper 4). Conclusion: The thesis recommends that violence prevention efforts should address the role of disability stigma, facilitate economically empowering opportunities for women living with disabilities in the country, and provide a range of accessible mental health services and GBV care and support services to facilitate better intimate partnership outcomes. Strengthened pathways to violence prevention and post-violence care and support should be coordinated by both disability and GBV sectors. The thesis calls for population data to reveal the prevalence and adverse public-health outcomes of GBV against women with disabilities in South Africa and other low-middle income countries (LMICs). Future epidemiological research should include validated disability measures and measures of disability-specific forms of violence that may compound GBV. Understanding the magnitude of violence against women with disabilities is the first step in the public-health approach to GBV prevention and requires collaborative research and surveillance efforts.